Odpowiedź :
proszę cię bardzo jeżeli będziesz mieć jakieś pytania dawaj śmiało
Odpowiedź:
[tex]1)\ \ 6x(2x-1)+4x(4-3x)=12x^2-6x+16x-12x^2=-6x+16x=10x\\\\\\2)\\\\\frac{3}{x}=\frac{5}{7}\ \ \ \ x\neq 0\\\\5x=21\ \ |:5\\\\x=\frac{21}{5}\\\\x=4\frac{1}{5}\\\\\\3)\\\\2x+17=26-x\\\\2x+x=26-17\\\\3x=9\ \ |:3\\\\x=3[/tex]
[tex]4)\\\\11-x=3x+8\\\\-x-3x=8-11\\\\-4x=-3\ \ |:(-4)\\\\x=\frac{3}{4}\\\\\\5)\\\\(3x+2)(2x+1)=(6x-3)(x+1)\\\\6x^2+3x+4x+2=6x^2+6x-3x-3\\\\6x^2+7x+2=6x^2+3x-3\\\\6x^2+7x-6x^2-3x=-3-2\\\\4x=-5\ \ |:4\\\\x=-\frac{5}{4}\\\\x=-1\frac{1}{4}[/tex]